Reminder of releasing advance payment upon fire protection coating - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the reminder of releasing advance payment upon fire protection coating for BRACU new campus project.